IMPLEMENTASI DAN EFEKTIVITAS MEDIASI NON-LITIGASI DALAM PENYELESAIAN SENGKETA - Margaretha Novalinda, Divanya Elizabeth (ADHAPER: Jurnal Hukum Acara Perdata, 2023)
Abstract Non-litigation mediation is a dispute resolution mechanism to reduce the burden on the courts and provide sustainable dispute resolution. Its effectiveness depends on regulations, institutions, and the level of professionalization of mediators. This study analyzes and compares the role of non-litigation mediators in the Indonesian and German legal systems in terms of the effectiveness of their implementation. This study uses a normative legal method with a comparative law approach, analyzed qualitatively and descriptively-analytically through primary, secondary, and tertiary legal materials. In Indonesia, non-litigation mediation has not been used optimally because it is not supported by specific laws, resulting in low professionalization of mediators. In contrast, Germany has comprehensively regulated mediation through the Mediationsgesetz, which recognizes mediators as an independent profession and positions mediation as the primary alternative to litigation with a relatively high success rate. This study concludes that strengthening non-litigation mediation in Indonesia requires regulatory consolidation, increased mediator professionalism, and institutional strengthening so that mediation functions effectively in the dispute resolution system. Keywords: non-litigation mediation; mediator; comparative law   Abstrak Mediasi non-litigasi merupakan mekanisme penyelesaian sengketa untuk mengurangi beban perkara pengadilan serta penyelesaian sengketa yang berkelanjutan. Efektivitasnya bergantung pada regulasi, institusional, dan tingkat profesionalisasi mediator. menganalisis dan membandingkan peran mediator non-litigasi dalam sistem hukum Indonesia dan Jerman yaitu pada efektivitas implementasinya. Penelitian ini menggunakan metode hukum normatif dengan pendekatan perbandingan hukum, dianalisis secara kualitatif dan deskriptif-analitis melalui bahan hukum primer, sekunder, dan tersier. Di Indonesia, mediasi non-litigasi belum digunakan secara optimal karena belum didukung undang-undang khusus, sehingga berdampak rendahnya profesionalisasi mediator. Sebaliknya, Jerman telah mengatur mediasi secara komprehensif melalui Mediationsgesetz, yang mengakui mediator sebagai profesi independen dan menempatkan mediasi sebagai alternatif utama litigasi dengan tingkat keberhasilan relatif tinggi. Studi ini menyimpulkan bahwa penguatan mediasi non-litigasi di Indonesia memerlukan konsolidasi regulasi, peningkatan profesionalisme mediator, dan penguatan kelembagaan agar mediasi berfungsi efektif dalam sistem penyelesaian sengketa. Kata Kunci: mediasi non litigasi; ediator; perbandingan;